2011
DOI: 10.1007/978-3-642-24971-6_10
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Cognition Analysis of the Ellsberg Paradox

Abstract: The 'expected utility hypothesis' is one of the foundations of classical approaches to economics and decision theory and Savage's 'Sure-Thing Principle' is a fundamental element of it. It has been put forward that real-life situations exist, illustrated by the 'Allais' and 'Ellsberg paradoxes', in which the Sure-Thing Principle is violated, and where also the expected utility hypothesis does not hold. We have recently presented strong arguments for the presence of a double layer structure, a 'classical logical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…During the last decade there has been an increasing evidence of presence of quantum structures in processes that find their origin in human behaviour and cognition, more specifically, in situations of decision making and in the structure of language (see, e.g., [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,25,23,24,26,27]). The success of this quantum modeling is interpreted as due to 'descriptive effectiveness of the mathematical apparatus of quantum theory as formal instrument to model cognitive dynamics and structures in situations where classical set-based approaches are problematical', without a priori a direct or precise connection with the validity of quantum laws in the microscopic world, although also recently a reflection connecting the quantum modeling in the micro-world with these new quantum cognition approaches has been put forward [27].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade there has been an increasing evidence of presence of quantum structures in processes that find their origin in human behaviour and cognition, more specifically, in situations of decision making and in the structure of language (see, e.g., [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,25,23,24,26,27]). The success of this quantum modeling is interpreted as due to 'descriptive effectiveness of the mathematical apparatus of quantum theory as formal instrument to model cognitive dynamics and structures in situations where classical set-based approaches are problematical', without a priori a direct or precise connection with the validity of quantum laws in the microscopic world, although also recently a reflection connecting the quantum modeling in the micro-world with these new quantum cognition approaches has been put forward [27].…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred from these results that in both cases, the unambiguous bet is more preferred to the ambiguous one. It is interestingly pointed out by Alerts et al (Aerts et al, 2011c;Aerts and Sozzo, 2012a,d), that, ambiguity, due to its contextuality, structurally needs a nonclassical probability model.…”
Section: Ellsberg Paradoxmentioning
confidence: 96%
“…Aerts et al, in a series of papers demonstrated the effectiveness of quantum-like modeling for the explanation of the irrationalities of human decision making in economics including the Ellsberg and Machina paradoxes (Aerts et al, 2011a(Aerts et al, , 2010(Aerts et al, , 2011cAerts and Sozzo, 2012a,d;.…”
Section: Ellsberg Paradoxmentioning
confidence: 97%
See 1 more Smart Citation
“…However, psychological and behavioral decision theoretical foundations of human decision making in the Newcomb's problem is still unknown. Recently, in order to model paradoxical human decisions in the situation such as the Prisoner's Dilemma (Rapoport and Chammah, 1965;Croson, 1999;Li et al, 2010), Ellsberg's urn problem (Ellsberg, 1961;Aerts et al, 2011) and two-stage gambling task , quantum decision theoretical models have been developed (Pothos and Busemeyer, 2009;Busemeyer et al, 2011). These quantum decisions theoretical studies revealed that human decision making is better accounted for by quantum probabilistic models in comparison to classical probabilistic models including Bayesian rational decision theory.…”
Section: Introductionmentioning
confidence: 99%